Selection of search strategies for solving 3-SAT problems - Pułka, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
The paper concerns the problem of Boolean satisfiability checking, which is recognized as one of the most important issues in the field of modern digital electronic system verification and design. The paper analyzes different strategies and scenarios of the proving process, and presents a modified and extended version of the autor`s FUDASAT algorithm.
Keywords: SAT solving; formal verification; CNF; Boolean satisfiability